Différents modes de confrontation à des traces de sa propre activité - Géraldine Rix-Lièvre (Revue d'anthropologie des connaissances)
This article explores the convergences and specificities of different methods which confront an actor with different traces of his activity. This methodological interrogation is part of a research which aims to study the course of a practice and its underlying knowledge. From different methods of verbalization of action, we propose to distinguish two ways. In order to study practice as it unfolds, we highlight advantages of a confrontation of the actor to a trace of its behavior and the difficulties it can also lead. To overcome them, we propose the construction of another trace of activity: a situated subjective perspective. We show advantages and limitations to confront an actor with this kind of trace. After all, we question widely the construction of traces of activity with an aim of verbalization of action.